2008
DOI: 10.1074/jbc.m709166200
|View full text |Cite
|
Sign up to set email alerts
|

Autoproteolytic Cleavage and Activation of Human Acid Ceramidase

Abstract: Herein we report the mechanism of human acid ceramidase (AC; N-acylsphingosine deacylase) cleavage and activation. A highly purified, recombinant human AC precursor underwent self-cleavage into ␣ and ␤ subunits, similar to other members of the N-terminal nucleophile hydrolase superfamily. This reaction proceeded with first order kinetics, characteristic of selfcleavage. AC self-cleavage occurred most rapidly at acidic pH, but also at neutral pH. Site-directed mutagenesis and expression studies demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 23 publications
1
62
0
Order By: Relevance
“…AC belongs to the N -terminal nucleophile (Ntn) hydrolase family ( 48 ). This family of enzymes shares the common feature of having an N -terminal nucleophile, which is generated by autoproteolytic processing ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…AC belongs to the N -terminal nucleophile (Ntn) hydrolase family ( 48 ). This family of enzymes shares the common feature of having an N -terminal nucleophile, which is generated by autoproteolytic processing ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Five human ceramidases have been cloned and are categorized by their optimal pH for in vitro activity as acid (ASAH1) and neutral (ASAH2) as well as three isoforms of alkaline (ACER1 to ACER3) (26,53,78). ASAH1 is a glycoprotein processed from a 55-kDa precursor into a heterodimeric protein formed by ␣ (14-kDa) and ␤ (40-kDa) subunits via autoproteolytic cleavage (3,66). In vivo studies demonstrated that ASAH1 requires sphingolipid activator proteins (SAP; saposin), mainly SAP-D, as cofactors for maximal activity (39).…”
mentioning
confidence: 99%
“…We have previously reported that the inactive AC precursor undergoes self-cleavage and activation, similar to other N-terminal nucleophile hydrolase family members (7). To the best of our knowledge this is the only mammalian ceramidase that is known to undergo this activation mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…We have recently shown that the inactive AC precursor undergoes self-cleavage to form a mature, active enzyme, and that the mechanism of this transformation is similar to other members of the N-terminal nucleophile hydrolase superfamily (7). Typically, the activity of one N-terminal nucleophile hydrolase subfamily member, the cysteine protease, is inhibited by small proteins known as cystatins (8).…”
mentioning
confidence: 99%